Spatial and temporal dynamics of the hydrology at Salinas Bay, Costa Rica, Eastern Tropical Pacific. - Rodríguez Badilla, Alejandro (2021)
Introduction: Salinas Bay is located in the warm pool of the Eastern Tropical Pacific (ETP), characterized by warm, shallow surface waters, a strong and shallow thermocline, and an important biological diversity. The primary productivity of the region is influenced by the coastal upwelling, which occurs during the boreal winter as a result of the strengthening of trade winds. Objective: To study the spatial and temporal dynamics of physical and chemical parameters at seven hydrographic stations in Salinas Bay, Costa Rica, through the analysis of CTD data, and relate the warm and cold events to the regional atmospheric conditions present when measuring the data. Methods: Seven hydrographic stations, sampled at Salinas Bay between August 2008 and December 2014, were selected. The variables processed for analysis are temperature, density, salinity, oxygen, chl-a and turbidity. Once the data was processed, 42 Hovmöller kind diagrams were plotted. Results: All variables, except turbidity, presented a seasonal periodicity associated with the upwelling. In general, colder and denser waters, higher salinity and chl-a concentrations and lower dissolved oxygen values were observed during the dry season, when the upwelling was active. Whereas, during the rainy season water masses were warmer and less dense, salinity and chl-a concentrations decreased and dissolved oxygen values tended to increase. Conclusions: The spatial and temporal dynamics of the hydrology in Salinas Bay was influenced by the coastal upwelling events. The region also presented an interannual variability associated with ENSO. Seasonal and interannual variability can counteract their effects on the oceanographic parameters when they coincide temporally.